Effect of drilling allowance on TBC delamination, spatter and re-melted cracks characteristics in laser drilling of TBC coated superalloys. (July 2016) - Fan, Zhengjie; Dong, Xia; Wang, Kedian; Duan, Wenqiang; Wang, Rujia; Mei, Xuesong; Wang, Wenjun; Cui, Jianlei; Yuan, Xin; Xu, Chengying
Abstract: Laser drilling of inclined holes on Ni-based superalloys coated with thermal barrier coatings (TBC) was studied using numerical simulation and experiments. Two types of drilling, three steps-laser drilling (TSLD) method and the one step laser drilling (OSLD), were employed for making comparison. The simulation results demonstrate that relatively strong vortex effect of assist gas at hole entrance and the drilling allowance of the substrate hole can deflect the trajectories of melt flow from leading edge TBC wall. This phenomenon may isolate leading edge of the hole from the ejecting molten material. Thus, shearing stress effect was prevented. The characteristics of TBC delamination, spatter at the TBC leading edge and re-melted cracks along the TBC trailing edge are investigated by comparing the characteristics of the melt flow obtained via simulation and experiment. The combined results suggest that the TBC/substrate multilayer can avoid these defects applying the TSLD technology. Highlights: Flow characteristics during the OSLD and TSLD process are investigated using CFD. "Vortex effect" of assist gas can deflect melt ejection away from TBC leading edge. Drilling allowance of substrate hole avoids molten flow of TBC leading edge. Formation mechanism of TBC delamination, spatter and remelted cracks are analyzed.